Determinants of Differential Voting Rights Share Prices and Ordinary Share Prices : Evidence from Dual-Class Companies in India - Faniband, Muhammadriyaj; Karthigai Prakasam, C. (Indian Journal of Research in Capital Markets, 2019)
We analyzed the effects of Indian factors namely, Nifty index, Volatility index (VIX), and Economic Policy Uncertainty Index (EPUI) and United States of America (USA) factors such as S&P 500 Index, CBOE VIX, and EPUI on differential voting rights (DVRs) share prices and ordinary share prices of three dual-class companies in India during the monthly period from January 2012-August 2019 using quantile regression approach. We found quite interesting and useful results. In case of dual-class shares of Jain Irrigation Systems, DVR share prices were significantly influenced by Nifty and S&P 500. In contrast, USA VIX and Indian & USA EPUI had less impact on DVRs. We noticed an insignificant dependence between India VIX and DVRs across different quantiles. Further, impact of Nifty, S&P 500, India VIX, USA VIX, and USA EPUI on ordinary share prices varied across the quantiles; whereas, India EPUI had no influence on ordinary shares’ prices. Regarding dual-class shares of Tata Motors, Nifty and S&P 500 had a significant impact on DVRs. However, DVRs were less sensitive to rest of the factors. For ordinary share prices, S&P 500 had a significant influence. However, the effects of other variables on ordinary share prices were not uniform across the quantiles. With respect to dual-class shares of Future Enterprises, both DVRs and ordinary share prices were highly affected by all the variables, except ordinary share prices were not exposed to India VIX.